Use of primers derived from a new sequence of the bovine Y chromosome for sexing Bos taurus and Bos indicus embryos - Alves, BCA; de Lima, VFMH; Teixeira, C. M.; Moreira, C. A. (Elsevier B.V., 2003)
A bovine male-specific marker was identified in our laboratory through random amplified polymorphic DNA (RAPD) analysis. This fragment of 3216 bp was cloned, sequenced and mapped by fluorescent in situ hybridization (FISH) on the taurine Yq. Primers derived from this sequence were initially screened by polymerase chain reaction (PCR) for their ability to detect Y-specific segments in zebu and taurine genomic DNA. Two of these primers amplified a 655 bp Y-specific sequence present in taurine and zebu male genomic DNA. These primers were then used for detecting the 655 bp male sequence in DNA from 173 zebu and 30 taurine embryos, which had been previously sexed using primers for the sequence BC 1.2. The results revealed an accuracy of 100%. (C) 2002 Elsevier B.V. All rights reserved.
Keywords: embryo sexing; Y-specific sequence; PCR